Two-dimensional crop flow separation model for rotor units of combine harvesters - Marvin Barther (agricultural engineering.eu, 2025)
Today, one-dimensional separation model approaches have been used successfully to estimate the separation efficiency for straw walkers and sieve-based cleaning units. In contrast to straw walkers, estimating the separation efficiency of rotor units with sensors is challenging, because straw and grain are transported along helical trajectories and sensors can only measure a small fraction of the separated grain. This study introduces a novel two-dimensional crop flow separation model based on Böttinger’s separation model and Wacker’s crop flow model for rotor units. Utilizing a large grid aligned sensor network of structure-borne noise sensors within the combine harvester’s rotor unit, the two-dimensional separation model approach fits well on grain masses within single rotor segments. It can be applied straightforwardly to different rotor unit designs and sensor positions.